Religiosity, Moral Licensing, and Overconfidence in Sharia-Compliant Investment Decisions: Experimental Evidence from Indonesia's Islamic Capital Market - Atika Lusi Tania; Einde Evana; Trijoko Prasetyo (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
: Sharia-compliant investment represents a growing domain of Islamic economic practice (muamalah), yet the behavioral dimensions governing Muslim investors' decision-making remain underexplored within Islamic law scholarship. This study examines whether overconfidence and religiosity — mediated by Self-Control Theory and Moral Licensing Theory — significantly influence investment decisions in sharia stock portfolio allocation. Employing a pure experimental design with a 2×2 factorial structure, overconfidence was manipulated through positive and negative feedback scenarios administered via a web-based platform, while religiosity was measured across five Islamic dimensions (ideology, ritual, intellectual, consequences, and experience) using an adapted Likert instrument. Investment decision quality was operationalized using the Sharpe Ratio as a portfolio performance proxy. Data from 80 participants were analyzed using ANOVA and ANCOVA, with normality, homogeneity, and linearity assumptions verified prior to testing. The results demonstrate three principal findings: first, investors with low overconfidence produced significantly superior Sharpe Ratio performance than those with high overconfidence; second, investors with low religiosity outperformed those with high religiosity in portfolio decision quality; and third, a significant interaction effect between overconfidence and religiosity was confirmed, indicating that their combined influence is non-additive. Notably, demographic covariates — including gender, age, and investment experience — exerted no significant effect on investment decisions, affirming that observed differences are attributable solely to experimental treatments. The theoretical contribution of this study lies in its novel application of Moral Licensing Theory to Islamic investment contexts, demonstrating that high religiosity may paradoxically impair financial decision-making by generating a psychological